Hedges and Boosters used by Becky Kennedy in the TED Talk - Rahmawati, Nofvy; Duwila, Shanty A.Y. P. S. (Lembaga Intelektual Muda (LIM) Maluku, 2024)
This research analyzes Becky Kennedy's use of hedges and boosters in the TED Talk